Appraisal of the Current Pharmacology Curriculum, Teaching Methodology and Effectiveness in Undergraduate Medical Education: A Student-Centric, Questionnaire-Based Study - Sarker, Sujit Kumar; Bhas, Geethanjali; Moitra, Priyanka; Paul, Ratna; Yusuf, Md. Abdullah; Marakala, Vijaya; Ratan, Zubair Ahmed; Ahmed, Ikramul; Arif, Khan Mohammad; Reza, AM Selim (Journal of Current and Advance Medical Research, 2021)
Background: Periodic students’ feedback ensures and enhances the effectiveness of the curriculum of medical subject. Objective: This study was designed to obtain students appraisal of the undergraduate pharmacology curriculum and teaching methodology. Methodology: This cross-sectional study was conducted in the Department of Pharmacology at Colonel Malek Medical College, Manikganj, Bangladesh from May to June, 2019 for a period of two months. Questionnaire-based data were collected from students of both sexes who had completed 3rd Professional examination. Likert Scale was applied to collect students’ feedback on pharmacology. Results: A total number of 40 students were recruited for this study of which 60.0% students were strongly agreed about organized teaching. About 47.5% students were agreed that the course was appropriate at their level and achieved their goals in Pharmacology. However, 55% of them strongly agreed that teacher provided clear constructive feedback during class. Total 60%, were agreed that the course improved their problem-solving skills. Overall, 55% students were agreed regarding their satisfaction on Pharmacology course delivery and conduction. Conclusion: In conclusion, periodic appraisal from students regarding evaluation of the student-centric undergraduate pharmacology curriculum is vital in developing efficient medical graduates. Journal of Current and Advance Medical Research, January 2021;8(1):30-33